ChemInform Abstract: Five‐Membered 2, 3‐Dioxo Heterocycles. Part 91. Reaction of 3‐Aroyl‐1H‐pyrrolo[2, 1‐c][1, 4]benzoxazine‐1, 2, 4‐triones with Dimedone. Crystalline and Molecular Structure of 3′‐Benzoyl‐4′‐hydroxy‐1′‐ (2‐hydroxyphenyl)‐6, 6‐dimethyl‐6, 7‐dihydrospiro [1‐benzofuran‐3, 2′‐pyrrole]‐2, 4, 5′(1′H, 5H)‐trione. Issue 24 (23rd May 2013) - Tutynina, N. M.; Racheva, N. L.; Maslivets, V. A.; Aliev, Z. G.; Maslivets, A. N.
Abstract The molecular structure of compound (III) is proved by X‐ray analysis.